Transcriptomics Underlying Pulmonary Ozone Pathogenesis Regulated by Inflammatory Mediators in Mice - Hye-Youn Cho; Anne E. Jedlicka; Frederick H. Chang; Jacqui Marzec; Alison K. Bauer; Steven R. Kleeberger (MDPI AG, 2021)
Ozone (O3) is the predominant oxidant air pollutant associated with airway inflammation, lung dysfunction, and the worsening of preexisting respiratory diseases. We previously demonstrated the injurious roles of pulmonary immune receptors, tumor necrosis factor receptor (TNFR), and toll-like receptor 4, as well as a transcription factor NF-κB, in response to O3 in mice. In the current study, we profiled time-dependent and TNFR- and NF-κB-regulated lung transcriptome changes by subacute O3 to illuminate the underlying molecular events and downstream targets. Mice lacking Tnfr1/Tnfr2 (Tnfr-/-) or Nfkb1 (Nfkb1-/-) were exposed to air or O3. Lung RNAs were prepared for cDNA microarray analyses, and downstream and upstream mechanisms were predicted by pathway analyses of the enriched genes. O3 significantly altered the genes involved in inflammation and redox (24 h), cholesterol biosynthesis and vaso-occlusion (48 h), and cell cycle and DNA repair (48-72 h). Transforming growth factor-β1 was a predicted upstream regulator. Lack of Tnfr suppressed the immune cell proliferation and lipid-related processes and heightened epithelial cell integrity, and Nfkb1 deficiency markedly suppressed lung cell cycle progress during O3 exposure. Common differentially regulated genes by TNFR and NF-κB1 (e.g., Casp8, Il6, and Edn1) were predicted to protect the lungs from cell death, connective tissue injury, and inflammation. Il6-deficient mice were susceptible to O3-induced protein hyperpermeability, indicating its defensive role, while Tnf-deficient mice were resistant to overall lung injury caused by O3. The results elucidated transcriptome dynamics and provided new insights into the molecular mechanisms regulated by TNFR and NF-κB1 in pulmonary subacute O3 pathogenesis.